PERANCANGAN SISTEM FORECASTING VOLUME PENJUALAN PRODUK RIBBON BARCODE MENGGUNAKAN METODE LEAST SQUARE PADA BINTANG BARKODE - Erlanda Antonius Andrian; Elis Sondang Dasawati (Institut Bisnis dan Informatika Kwik Kian Gie, 2021)
Forecasting is an art and science in predicting future events. In this study, the authors used the sales volume forecasting with the least square method to calculate sales forecasting based on promotional costs and time trends. The data sources in this study are ribbon barcode sales data and Barkode Star promotion costs obtained through structured interviews and participatory observations, and secondary data from library studies. Then the results of thesales volumeforecast will be displayed into text and web-based visual graphics. This research will show the results of sales forecasting based on promotional costs and time trends. Both forecasting results will be a consideration in the future for the Barkode Star in making a decision. Forecasting is done with a web-based application specifically created for Barkode Star as needed by the company.